Breast silicone implants’ pericapsular impairment: current underdiagnosed status - de Faria Castro Fleury, Eduardo (Frontiers in Surgery, 2023)
Since the end of the breast implants moratorium at the beginning of the 21st century, the number of surgeries using silicone implants has increased exponenally. Currently, groups of women gathered on social networks associang their morbidies with the presence of breast silicone implants. One of the main complaints of paents with clinical symptoms related to silicone implants is the difficulty in diagnosing the disease.The descriptors in the BI-RADS lexicon seem outdated for classifying the new generaons of implants with cohesive gel, which hinders the diagnosis of device complicaons. In this review we show the most common impairment of the pericapsular space of the silicone implants, usually ignored in the MRI analysis.